Rancang Bangun Penerapan Smart Relay Berbasis Mikrokontroller - Miftah Hadi R Harahap (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
Lights are not just lighting at night, but have also developed into an addition to the aesthetic value of the garden. We can choose various models and styles according to our needs, as is the case with fashion developments which are always up to date and changing fashions, lighting trends or lights also experience the same thing. This is the same as the function of decorative lights in general which can be adapted to the design and size of the garden, not only that the garden house will never be separated from lighting. The shape of a garden with a broad and minimalist tropical style will be very meaningful if the lighting equipment is fulfilled and fits.